Spiritualiteit in het Lucasevangelie: verscheidenheid en gemeenschap - H. Welzen (Acta Theologica)
The themes in the Gospel of Luke connected to building up the community are important for the intended readers who, in the last quarter of the first century, were part of Christian communities which comprised various groups. Among them there were differences in social and economic positions and in cultural and religious origins. For these intended readers the themes of poverty and wealth were of great importance. Poverty and wealth relate in the first instance to economic positions. But they could also denote spiritual openness or spiritual closeness. While the poor are oriented towards God, the rich are oriented toward themselves and focused on preserving their future. Jesus’ contact with tax collectors and sinners, and the Pharisees’ and scribes’ opposition towards this behavior, mirror the social contact with people who have hardly or no prestige in the Christian community. Table companionship in which everyone, whatever his or her position, is allowed to participate is not only realized in Jesus’ relationship with real people, it is also an image of the eschatological realization of the Kingdom of God. For the Christian communities with their many groups at the end of the first century, the liberating initiative of God becomes concrete in a community spirituality with its concern for the poor, the lowly, the not esteemed and the oppressed. This spirituality is messianic and prophetic. It is rooted in the orientation on God who has solidarity with the poor and the oppressed. At the same time this community spirituality is eschatological. For those who accept the announcement of liberation this liberation is completely realized in the coming of the Son of Man.